2021
DOI: 10.1186/s12864-020-07299-y
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun proteomics of peach fruit reveals major metabolic pathways associated to ripening

Abstract: Background Fruit ripening in Prunus persica melting varieties involves several physiological changes that have a direct impact on the fruit organoleptic quality and storage potential. By studying the proteomic differences between the mesocarp of mature and ripe fruit, it would be possible to highlight critical molecular processes involved in the fruit ripening. Results To accomplish this goal, the proteome from mature and ripe fruit was assessed fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 145 publications
(189 reference statements)
1
8
0
Order By: Relevance
“…These authors, by using a proteomic approach on peach ripening fruit, identified a P. persica homologue of a GUANYLATE-BINDING PROTEIN1 (SlGBP1) (Prupe.4G053400, 70.6% identity), a tomato protein able to maintain endopolyploid cells in a non-proliferative state [56], which was accumulated with the progression of ripening. This result indicates that endopolyploid cells division would be inhibited in the last phase of peach fruit development [55] and is consistent with our cytofluorimetric analysis result on S4 FAN fruits (Figure 1c and Figure S1). Indeed, in S4 FAN fruit the proportion of clearly endoreduplicated cells (sum of 8C-32C populations) account for 39%, a much lower value than that observed in ripening tomato fruit, in which the number of endoreduplicated cells (sum of 8C-256C populations) was more than 85% of total pericarp cells [57].…”
Section: Endoreduplication Processes Slight Affect Peach Fruits Sizesupporting
confidence: 91%
See 2 more Smart Citations
“…These authors, by using a proteomic approach on peach ripening fruit, identified a P. persica homologue of a GUANYLATE-BINDING PROTEIN1 (SlGBP1) (Prupe.4G053400, 70.6% identity), a tomato protein able to maintain endopolyploid cells in a non-proliferative state [56], which was accumulated with the progression of ripening. This result indicates that endopolyploid cells division would be inhibited in the last phase of peach fruit development [55] and is consistent with our cytofluorimetric analysis result on S4 FAN fruits (Figure 1c and Figure S1). Indeed, in S4 FAN fruit the proportion of clearly endoreduplicated cells (sum of 8C-32C populations) account for 39%, a much lower value than that observed in ripening tomato fruit, in which the number of endoreduplicated cells (sum of 8C-256C populations) was more than 85% of total pericarp cells [57].…”
Section: Endoreduplication Processes Slight Affect Peach Fruits Sizesupporting
confidence: 91%
“…For each genotype, the fruit cross diameter of 100 fruits distributed on five trees was monitored on average weekly throughout development over the 2016 growth season, starting measurements 41 days after full bloom (DAFB), up to 132 DAFB to monitor the fruit growth. A total of 13 time points were obtained, i.e., at 41,48,55,62,69,83,90,97,104,111,118,125, and 132 DAFB. On each sampling date, at least 15 fruits were always harvest from the same five trees (for each cultivar), and then the fruits were split in 3 biological replicates, each composed of 5 fruits.…”
Section: Plant Material Samples and Cytological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…From the list of proteins, it is evident that the majority of the proteins have fundamental roles in sugar synthesis, thus, it is confirmed that peach plants protect themselves from the freezing conditions by synthesizing various sugar compounds, which can also be related to photosynthesis and respiration [ 68 ]. In addition, shotgun proteomics using 1D-gel (PAGE-SDS), combined with LC/MS-MS analysis, revealed 131,435 spectra that can be further matched against available stress tolerance datasets to generate freeze-tolerant datasets [ 69 ]. Furthermore, the PTMs of various proteins involved in stress response can be identified using the combined omics techniques, which will provide more valuable data for investigating stress tolerance [ 70 ].…”
Section: Proteomicsmentioning
confidence: 99%
“…Large-scale proteomics has been providing new information for fundamental biology [1,2], and in several related sciences such as toxicology [3,4], animal physiology and pathology [5], food safety, and aquaculture [6][7][8]. It has been providing insights concerning the mechanisms underlying several diseases [9,10].…”
Section: Introductionmentioning
confidence: 99%